The Terrible Two go wild - Barnett, Mac; John, Jory (Barnett, Mac. Terrible Two., 2018)
"School's out, and Miles and Niles are running wild in the woods outside town: climbing trees, exploring caves, and, yes, pranking. But these leafy, lazy days of mischief darken when bully Josh Barkin and his cadets from a nearby kids' boot camp discover the merrymakers--and vow to destroy them"--